The effects of foliar application of boron, potassium, and marine algae on the nutrient contents, and vitamin C - Kousa, Tahani; Kharbotl , Rashid; Boessa, Boessa (Jordan Journal of Agricultural Sciences, 2025)
This study was carried out in Lattakia on apple fruit tree (Golden delicious variety) during 2021 and 2022 growing seasons to assess the effect of foliar application with nutrients on the apple fruit content of nutrients and vitamin C, The experiment involved eight treatments where spraying with boron, potassium and seaweed extract was done individually or in combination with each other, The percentage of fruit content of nitrogen increased morally when sprayed with marine algae extract 0.414% for the average two years compared to the control 0.288 %, also gave the treatment of blending boron, potassium, marine algae extract and the treatment of marine algae extract the highest fruit content of phosphorus 0.084%, 0.087% control 0.058%, The fruit content of potassium boron mixture Boron mixture outweighed the rest of the treatments for the average two years 1.555% for the fruit content of calcium outweighed the mixing treatment between boron control 1.201%, potassium and marine algae 0.055% the control gave 0.043%. the magnesium content outperformed the rest of the treatments, while the control was 0.043%, 0.035%. For boron content, the mixing treatment between boron, potassium, and marine algae outperformed the rest of the treatments and was 27.232 PPM, the control was 23,76 PPM. Vitamin C increased in fruits in different treatments, boron-potassium-phosphorus 16.87 mg/100ml compared to the control 16.87 mg/100ml.